2023
DOI: 10.1002/mabi.202200502
|View full text |Cite
|
Sign up to set email alerts
|

ROS Scavenging Graphene‐Based Hydrogel Enhances Type H Vessel Formation and Vascularized Bone Regeneration via ZEB1/Notch1 Mediation

Abstract: The regeneration strategy for bone defects is greatly limited by the bone microenvironment, and excessive reactive oxygen species (ROS) seriously hinder the formation of new bone. Reduced graphene oxide (rGO) is expected to meet the requirements because of its ability to scavenge free radicals through electron transfer. Antioxidant hydrogels based on gelatine methacrylate (GM), acrylyl-𝜷-cyclodextrin (Ac-CD), and rGO functionalized with 𝜷-cyclodextrin (𝜷-CD) are developed for skull defect regeneration, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Excessive in ammation and ROS can prolong the in ammatory period during wound healing, resulting in wound delayed or non-healing 32 . Therefore, wound repair materials should have certain ROS scavenging ability.…”
Section: Resultsmentioning
confidence: 99%
“…Excessive in ammation and ROS can prolong the in ammatory period during wound healing, resulting in wound delayed or non-healing 32 . Therefore, wound repair materials should have certain ROS scavenging ability.…”
Section: Resultsmentioning
confidence: 99%
“…Zhou et al utilized a reduced graphene oxide hydrogel (GM/Ac-CD/rGO) in a mouse cranial defect model. They found that the hydrogel could enhance the immune microenvironment by neutralizing free oxygen radicals (ROS) around the cranial defect through the electron transfer capacity of reduced GO [ 101 ]. In a study by Hang Xue et al, it was demonstrated that quaternized chitosan-graphene oxide-polydopamine nanocomposites (QCS-GO-PDA) significantly scavenged ROS and reduced inflammatory responses.…”
Section: Potential Mechanisms and Related Signaling Pathways Of Graph...mentioning
confidence: 99%